CD4+CD25+Treg Cells Prolong the Survival Time of Heart Allograft Via Induction Lymphocyte Apoptosis and Modulation the Ratio of T Cell Subsets - Zhu, Jinguo; Xiong, Lihua (Cardiology and Cardiovascular Medicine, 2022)
Background: CD4+CD25+regulatory T cells (CD4+CD25+ Treg cells) play major roles in immune regulation. Previous studies showed CD4+CD25+ Treg cells can maintain peripheral immune tolerance and increase the survival time of transplanted organs. However, the biological characteristics and the functional roles of these CD4+CD25+ Treg cells in transplantation tolerance remain unknown. The current study was conducted to observe the effect of CD4+CD25+ Treg cells on heart allograft in rats and to investigate the underlying mechanism of the CD4+CD25+ Treg cells. Methods: 5 x 107 spleen cells of SD rats were inoculated into the thymus gland of Wistar rats. The level of CD4+CD25+ Treg cells was examined by the flow cytometry method, and the biological activity of CD4+CD25+ Treg cells was detected by the 3H-TdR method. Hearts were transplanted from SD rats (donors) to Wistar rats (recipients) and the animals were assigned into four groups: HT, HT+Ii,HT+Treg, HT+Treg+Ii. At various time points after the transplantation, the transplanted hearts were collected and histologically examined. The rate of lymphocyte apoptosis and T cell subsets in the peripheral blood of Wistar rats were analyzed with flow cytometry. Results: The CD4+CD25+ Treg cells in Wistar rats were sharply increased, and these CD4+CD25+ Treg cells significantly extended the survival time: The mean survival time of the transplanted hearts was 8.1 ± 1.2 days, 35.7 ± 4.7 days, 53.7 ± 6.2 days, 75.7 ± 11.3 days in the group of HT, HT+Ii, HT+Treg, or HT+Ii+Treg, respectively (n = 12-14/group). Among them, the survival time between HT and HT+Treg or betwee